Analysis Of The Level Of Understanding Of The Staff PT Gapura Angkasa Is Facing Signage At The Domestic Terminal Of Juanda Surabaya International Airport - Mohammad Syahril Abd. Rahman; Teguh Ariebowo (Pusat Riset dan Inovasi Nasional, 2024)
PT Angkasa Pura I is the manager of several airports, including Juanda Surabaya International Airport. One business that supports airport operations in the field of service providers is PT Gapura Agkasa. Signage is required as a smooth transition between the airport and the city because of the size of Juanda International Airport. All airport users can improve traffic or activity in the area by being well-versed in the signage. The purpose of the study is to evaluate the comprehension level of the Gapura Space employees working at Juanda Surabaya International Airport's Domestic Terminal. In this study, the researchers used quantitative descriptive research methods. The researchers use documentation and questionnaires as data collection techniques of 20 questions, and data analysis techniques as statistics. The sample in this study is the staff of the PT Gapura Space at Juanda Surabaya International Airport of 82 respondents. The results of this study showed the level of understanding of the Space Gapura staff of the Signage at the Domestic Terminal of Juanda Surabaya International Airport with a percentage of 91.52%. From that it can be stated that the staff of P.T. Gapura Space has a very high level of understanding of Signage at the Domestic Terminal of Juanda Surabaya International Airport.